2015
DOI: 10.1007/s11104-015-2536-z
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging tolerance in barley is associated with faster aerenchyma formation in adventitious roots

Abstract: Background and aims Plant adaptation to waterlogged conditions requires a set of morphological and physiological/biochemical changes. The formation of aerenchyma is one of the most crucial adaptive traits for waterlogging tolerance. Enzymatic scavenging may also potentially contribute to waterlogging tolerance by providing detoxification of reactive oxygen species (ROS). Methods Changes of root porosity (as an indicator of aerenchyma formation) and activities in leaves of four major antioxidant enzymes, γ-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 84 publications
3
67
1
Order By: Relevance
“…The production of ARs is an important adaptive trait for waterlogging tolerance (Zhang et al, 2015;Steffens and Rasmussen, 2016). Adventitious roots are induced by waterlogging to channelize the transportation of air diffused in the stem portion to the root (Visser et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The production of ARs is an important adaptive trait for waterlogging tolerance (Zhang et al, 2015;Steffens and Rasmussen, 2016). Adventitious roots are induced by waterlogging to channelize the transportation of air diffused in the stem portion to the root (Visser et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Aerenchyma is a characteristic feature of Typha domingensis, as of many other hydrophytes of aquatic saline wetlands (Zhang et al 2015b). One of the most common effects of increasing stress tolerance was the formation of aerenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…After 1 d of salinity, malate but not citrate increases, whereas after 3 d of salinity, both 2-oxoglutarate and succinate accumulate, even though GABA presumably does not contribute directly to the succinate pool in this mutant (Renault et al 2010). Cold stress, as well as waterlogging, flooding and hypoxia, which simulate an O 2 deficit, cause the accumulation of both GABA and succinate, and occasionally citrate, fumarate and malate (Kaplan et al 2007;Rocha et al 2010;Komatsu et al 2011;Antonio et al 2016) (Fig. 2).…”
Section: Respiratory Processesmentioning
confidence: 99%
“…1). Indeed, evidence has shown that GHB accumulates with oligomycin inhibition of mitochondrial ATP synthase (Geisler et al 2012), as well as cold (Kaplan et al 2007) (Fig. 2) and various other abiotic stresses, including O 2 deficit, waterlogging, heat, drought and UV (Allan et al 2003(Allan et al , 2008(Allan et al , 2012Breitkreuz et al 2003;Fait et al 2005).…”
Section: Ghb Metabolismmentioning
confidence: 99%